Irène, Scut, Magritte and C° : Het bekoorlijke is mooi. - Adriaens-Pannier, Anne; Albert, Inge; Andujar Alfonso, Anne; Baudson, Pierre; Bussy, Christian; Canonne, Xavier; Colin-Boon, Micheline; Coomans-Cardon, Véronique; Daems, Catherine; De Haes, Frans; De Wilde, Eliane; Delaunois, Alain; et al. (Brussel : Koninklijke Musea voor Schone Kunsten van België Brussel, 1996)
Abeele, Remy Van Den ; Alechinsky, Pierre ; Van Assche, Petrus ; Baele, Alfons ; Baes, Rachel ; Bardelli, Gino Giovanni ; Blavier, André ; Bossut, Yves ; Bouché, Paul ; Bousquet, Joe ; Brenta, Gilles ; Breton, André ; Broodthaers, Marcel ; Van Bruaene, Gérard ; Bury, Pol ; Bussy, Christian ; Canon, Luc ; Canonne, Xavier ; Caso, Paul ; Char, René ; Chavée, Achille ; Colinet, Paul ; Danielle ; Dard, Frédéric ; Deble, Colette ; Deknop, Evelyn ; Deknop, Georges-François ; Delcol, Roland ; Delvaux, Paul ; Depoorter, Luc ; Dewez-Van Den Abeele, Claudine ; Dumont, Fernand ; Dunbar, Pol ; Eemans, Marc ; Eluard, Paul ; Gérard, Françoise ; Goemans, Camille ; Graverol, Jane ; Gutt, Tom ; Haustrate, Gaston ; Jamagne, Claudine ; Labisse, Félix ; Lecomte, Marcel ; Lenoir, R. ; Lepri, Stanislao ; Lucassen, Ludwig ; Magritte, Aline ; Magritte, Paul ; Magritte, René ; Malva, Constant ; Mariën, Georges ; Mariën, Marcel ; Marion, Denis ; Mesens, E.L.T. ; Milo, Jean ; Nougé, Paul ; De Pauw, Jef ; Permantier, Armand ; Raine, Jean ; Rapin, Maurice ; Rouge, Paul ; Rouveyre, André ; Roux, Georges-Louis ; Sanders, Pierre ; Servais, Max ; Simon, Armand ; Souris, André ; Stas, André ; Tanguy, Yves ; Ubac, Raoul ; Walemont ; Wergifosse, Jacques ; Willems, Robert ; de Wouwer, Roger van
René Magritte : "Het bekoorlijke is mooi". Irène, Scut, Magritte and C°, Koninklijke Musea voor Schone Kunsten van België, Brussel, van 13 september tot 15 december 1996
Frans
Nederlands
Nederlands & Frans
boek
Keywords: Magritte, René